Three essays in regional economics: migration, regional portfolio theory, resilience, and agglomeration economies - Care, Jonathan Charles, author; Weiler, Stephan, advisor; Braunstein, Elissa, committee member; Pena, Anita Alves, committee member; Thilmany, Dawn, committee member (Colorado State University. Libraries, 2023)
Cities and counties are dynamic entities that experience constant change, generated from both local and external forces. Some locations are rich in natural amenities, others are powerhouses of manufacturing or provide a rich level of services and quality of life to their citizens. Each location maintains a unique set of characteristics that makes it appealing to a given slice of the population and set of business enterprises. Understanding these characteristics and patterns of migration is a substantial focus in the field of regional economics. Researchers attempt to enhance our understanding by examining this phenomenon through a number of different lenses. Some have examined flows to the largest cities in the country and tried to uncover the underlying reasons for the unique advantages these metropolitan areas possess. Others have examined various measures of risk and reward to see which cities or counties outshine their competitors. Still others attempt to measure the appeal of regions by quantifying their natural amenities or investigating their resilience to negative economic events. Recent global events have brought understanding a number of these regional performance topics to the forefront of both academic and mainstream interest. This dissertation examines several aspects of regional economics with an aim to move the conversation forward along several tracks. The first chapter explores the contribution of regional employment portfolio risk and return measures in a case study of county level migration into Colorado. The level of employment data used in the construction of the employment portfolio measures is varied to see which level of aggregation best contributes to the understanding of migration flows. The results show that the employment portfolio composition of a county does play a role in attracting migrants and highlight interesting findings on economy-wide risk versus individual potential returns. Additionally, we find evidence of labor pooling and agglomeration effects for Colorado's largest counties. A lack of cohesion and consistency across sector-level measures of risk and return suggests that local governments should focus on creating a stable overall business environment, rather than attempting to focus on specific sectors. The second chapter discusses the concept of economic resilience and how it complements discussions relating to regional economic growth. A total of seven models are tested, split between two different formulations of measuring resilience. Testing is performed to identify a set of independent variables that robustly contribute as explanatory determinants of resilience. The results identify several determinants of resilience that are robust across different definitions of economic resilience and provide insights that can be used by local policy makers when considering the tradeoffs between balancing growth and resilience. The chapter ends with a discussion of the strengths and weaknesses of existing measures of resilience and the advantages of future work in this area. The final chapter of the dissertation examines the dual, decades-long decline in both migration rates and the level of economic dynamism within the United States. Specifically, the role of information generated by the churn of resources through the economy is explored within the context of county and metropolitan statistical area (MSA) in-migration rates. The difference in average annual in-migration rates is also examined using a three-fold Blinder-Oaxaca decomposition. This study finds that locally generated information on dynamism does contribute to the decision of whether to migrate. In particular, the findings show a unique role for information gained from regional dynamism when considering migration to smaller metropolitan areas, likely resulting from the more homogeneous identity these regions maintain, in comparison to larger, more multi-faceted, metropolitan areas. The overarching goal of this work is to contribute to the literature on why individuals choose to live where they do. The topics examined over the course of this dissertation permeate several veins of the regional economic literature. However, they all work together in the service of the question "what makes a place attractive to in-migrants?" This is accomplished by looking at the risks and returns to regional employment portfolios, the degree to and speed with which regions rebound from recessions, and how information generated by the churn of resources through the economy helps in the decision to migrate. These topics represent three of the drivers among the broad portfolio of factors regional economics utilizes to try and understand behavior within a country.